2020
DOI: 10.1096/fj.201902833r
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cGAS homologs in innate and adaptive mucosal immunities in zebrafish gives evolutionary insights into cGAS‐STING pathway

Abstract: Cyclic GMP‐AMP synthase (cGAS) is one of the most‐characterized cytoplasmic DNA sensors in humans and other mammals. However, knowledge about cGAS homologs in nonmammalian species remains limited. In this study, we report the molecular and functional identification of two cGAS homologs, namely, DrcGASa and DrcGASb, from a zebrafish (Danio rerio) model. DrcGASa and DrcGASb share the same overall conservative structural architectures and functional domains/residues to mammalian cGASs. Both homologs synthesized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 60 publications
0
24
1
Order By: Relevance
“…implying that other reported sensors may be poorly relevant in vivo. Activation of cGAS zebrafish isoforms also triggers synthesis of cGAMP and activation of STING-mediated IFN responses in vitro and in vivo [40]. These recent data contrast with previously reported DNA sensing mechanisms in zebrafish larvae.…”
Section: I1 Type I Interferon Production In Health and Diseasecontrasting
confidence: 77%
See 1 more Smart Citation
“…implying that other reported sensors may be poorly relevant in vivo. Activation of cGAS zebrafish isoforms also triggers synthesis of cGAMP and activation of STING-mediated IFN responses in vitro and in vivo [40]. These recent data contrast with previously reported DNA sensing mechanisms in zebrafish larvae.…”
Section: I1 Type I Interferon Production In Health and Diseasecontrasting
confidence: 77%
“…Characterized zebrafish orthologues of mammalian cGAS were dispensable in this context [41], although STING was essential as in humans and mice [34,39]. These data are contrasted with the ability of zebrafish cGAS orthologues to synthesize cGAMP and activate STING-mediated IFN signalling in response to DNA stimulation [40].…”
Section: Ii1 Models Of Inflammatory Disordersmentioning
confidence: 97%
“…To date, there are six classes of PRRs which are categorized based on shared structural elements: toll-like receptors (TLRs), C-type lectin receptors (CLRs), NOD-like receptors (NLRs), AIM2-like receptors (ALRs), RIG-I-like receptors (RLRs) and cGAS/STING receptors (reviewed in [ 41 ]). Though not as well understood as their mammalian counterparts, receptors from all but the ALRs have been identified in teleosts [ 43 , 44 , 45 , 46 , 47 ]. Although there are some similarities between mammalian and teleostean PRRs, some discrepancies do exist.…”
Section: Teleostean Immunity: Our Current Understanding Of the Antmentioning
confidence: 99%
“…cGAS is conserved in various species spanning from fish to mammals. In teleosts, the N-terminal region of the cGAS protein is markedly conserved, while the amino acids involved in the DNA-binding surface and cGAMP synthesis in the mab21 domain are also highly conserved [ 105 , 160 ].…”
Section: Cgasmentioning
confidence: 99%
“…Although, the zebrafish cGAS homologue has low amino acid identity to human cGAS (less than 35%), their similar activities were determined [ 179 ]. Liu and co-workers [ 160 ] reported that overexpression of zebrafish cGASa/b in HEK293T cells and zebrafish embryos significantly activated NF-κB and type I IFN signaling pathways in a STING-dependent manner, and that cGASa, but not cGASb, was involved in immunoglobulin Z-mediated mucosal immunity in gill-associated lymphoid tissue, suggesting differential functions between the two DrcGASs [ 160 ]. Interestingly, it was revealed that the ortholog of cGAS in grass carp, cGAS-like (cGASL) by interacting with STING down-regulates transcription of type I IFN gene and functions as a negative regulator of IFN response.…”
Section: Cgasmentioning
confidence: 99%